Heterostructured TiO2 Nanorod@Nanobowl Arrays for Efficient Photoelectrochemical Water Splitting. Issue 11 (18th January 2016) - Wang, Wenhui; Dong, Jingya; Ye, Xiaozhou; Li, Yang; Ma, Yurong; Qi, Limin
Abstract : Heterostructured TiO2 nanorod@nanobowl (NR@NB) arrays consisting of rutile TiO2 nanorods grown on the inner surface of arrayed anatase TiO2 nanobowls are designed and fabricated as a new type of photoanodes for photoelectrochemical (PEC) water splitting. The unique heterostructures with a hierarchical architecture are readily fabricated by interfacial nanosphere lithography followed by hydrothermal growth. Owing to the two‐dimensionally arrayed structure of anatase nanobowls and the nearly radial alignment of rutile nanorods, the TiO2 NR@NB arrays provide multiple scattering centers and hence exhibit an enhanced light harvesting ability. Meanwhile, the large surface area of the NR@NB arrays enhances the contact with the electrolyte while the nanorods offer direct pathways for fast electron transfer. Moreover, the rutile/anatase phase junction in the NR@NB heterostructure improves charge separation because of the facilitated electron transfer. Accordingly, the PEC measurements of the TiO2 NR@NB arrays on the fluoride‐doped tin oxide (FTO) substrate show significantly enhanced photocatalytic properties for water splitting. Under AM1.5G solar light irradiation, the unmodified TiO2 NR@NB array photoelectrode yields a photocurrent density of 1.24 mA cm –2 at 1.23 V with respect to the reversible hydrogen electrode, which is almost two times higher than that of the TiO2 nanorods grown directly on the FTO substrate. Abstract : Heterostructured TiO2 nanorod@nanobowl arrays consisting of rutile TiO2 nanorods grown on the inner surface of arrayed anatase TiO2 nanobowls are designed and fabricated as a new type of 3D‐structured photoanode for photoelectrochemical water splitting, which possess multiple scattering centers, increased electrolyte accessible surface area, and beneficial anatase–rutile heterojunctions.